The foreign correspondent a novel - Furst, Alan (New York Random House, 2006)
The Foreign Correspondent is the story of a handful of antifascists: the army officer known as "Colonel Ferrara," who fights for a lost cause in Spain; Arturo Salamone, the shrewd leader of a resistance group in Paris; and Christa von Schirren, the woman who becomes the love of Weisz's life, herself involved in a doomed resistance underground in Berlin.

The Foreign Correspondents is Alan Furst at his absolute best--taut and powerful, enigmatic and romantic, with sharp, seductive writing that takes the reader through darkness and intrigue to a spectacular denouement.
Keywords: Germany. -- Geheime Staatspolizei -- Fiction; Ovra (Organization : Italy) -- Fiction; Journalists -- France -- Paris -- Fiction; Underground newspapers -- France -- Paris -- Fiction; Europe -- History -- 1918-1945 -- Fiction